Anticonvulsant drug–induced cell death in the developing white matter of the rodent brain. (25th March 2016) - Kaushal, Suhasini; Tamer, Zenab; Opoku, Freda; Forcelli, Patrick A.
Summary: Objective: During critical periods of brain development, both seizures and anticonvulsant medications can affect neurodevelopmental outcomes. In rodent models, many anticonvulsants trigger neuronal apoptosis. However, white matter apoptosis (WMA) has not been examined after anticonvulsant drug treatment. Herein, we sought to determine if anticonvulsant drugs induced apoptosis in the developing white matter (WM) in a rodent model. Methods: Postnatal day (P)7 rats were treated with phenobarbital (PB‐75), MK‐801 (dizocilpine, 0.5), lamotrigine (LTG‐20), carbamazepine (CBZ‐100), phenytoin (PHT‐50), levetiracetam (LEV‐250), or saline; all doses are mg/kg. Brain tissue collected 24 h after treatment was stained using the terminal deoxynucleotidyl transferase dUTP nick end labeling method. The number of degenerating cells within WM, that is, anterior commissure (AC), corpus callosum, cingulum, and hippocampus‐associated WM tracts, was quantified. Results: Saline‐treated rats showed low baseline level of apoptosis in developing WM on P8 in all the areas examined. PB, PHT, and MK‐801 significantly increased apoptosis in all four brain areas examined. Exposure to CBZ, LTG, or LEV failed to increase apoptosis in all regions. Significance: Commonly used anticonvulsants (PB, PHT) cause apoptosis in the developing WM in a rat model; the N ‐methyl‐d ‐aspartate (NMDA) receptor antagonist MK‐801 has a similar effect. These results are consistent with reports of anesthesia‐induced WMA during brain development. Consistent with the lack of neuronal apoptosis caused by LTG, LEV, and CBZ, these drugs did not cause WMA. Many infants treated with anticonvulsant drugs have underlying neurologic injury, including WM damage (e.g., following intraventricular hemorrhage [IVH] or hypoxic‐ischemic encephalopathy [HIE]). The degree to which anticonvulsant drug treatment will alter outcomes in the presence of underlying injury remains to be examined, but avoiding drugs (when possible) that induce WMA may be beneficial.